KUALITAS FISIK DAGING SAPI DARI TEMPAT PEMOTONGAN HEWAN DI BANDAR LAMPUNG - Nikodemus Prajnadibya Kurniawan; Dian Septinova; Kusuma Adhianto (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2014)
The research was conducted in April 2014 in slaughterhouses in Bandar Lampung. This studyaims to determine the physical quality of the beef that is in Bandar Lampung by pH, water holdingcapacity and cooking loss. The meat is taken from the back of the thigh meat obtained fromslaughterhouses in Bandar Lampung. This study uses survey were analyzed descriptively.The results showed that the physical quality of the beef that is in Bandar Lampung is stillwithin the normal range. Average pH of 6.0, while the average value of 30.14 water holding capacity,and the average value of 42.53 cooking shrinkage. Based on these results it can be concluded that(1)the physical quality of the beef slaughtering place is normal and (2)good to eat.